COVID-19 Case Investigation and Contact Tracing Programs and Practice: Snapshots From the Field. Issue 4 (18th July 2022) - Harper-Hardy, Paris; Ruebush, Elizabeth; Allen, Meredith; Carlin, Maggie; Plescia, Marcus; Blumenstock, James S.
Abstract : Between Fall 2020 and Spring 2021, the Association of State and Territorial Health Officials conducted 2 rapid queries to collect information from the field regarding the status of COVID-19 case investigation and contact tracing (CI/CT) programs and practice. These short surveys were distributed to senior deputies in state and territorial health agencies, yielding a response rate of 45.8% (November 2020) and 40.7% (April 2021). Findings indicated that CI/CT staff roles and assigned functions varied across jurisdictions, as did staffing levels/capacity, approaches for linking individuals to social supports, and program changes that were planned or underway. Agency-reported staffing levels/capacity and programmatic challenges changed over time, highlighting the dynamic nature of CI/CT program practice and implementation. While findings from the surveys cannot be generalized to the national level, they provide critical insights from the field on CI/CT program implementation, challenges, and changes in response to the evolving COVID-19 epidemic in the United States.